Calculation Of Incident Management Maturity Level At PT XYZ Using ITILv3 Framework - Nurhasanah, Eva (Journal Research of Social Science, Economics, and Management, 2023)
One of the keys to successful information technology (IT) is good IT service management planning [1]. Implementation of ITIL also makes IT functions more valueable and user oriented, better structure and coordination in IT functions through standardization and process documentation, clear roles and responsibilities, better synchronization of various IT services and increased transparency. PT XYZ is one of the IT companies and the largest data center service provider in Indonesia. Improving service quality is a target for companies to provide good services to the IT services. Based on data in 2022, from the ITS Division, the average incident report that can be completed on time is around 78% from all services reported in IT Services. Based on the data obtained, it is necessary to evaluate the measurement of the maturity level of IT services that have been implemented at PT XYZ. The results of the overall process maturity level based on the maturity assessment used in handling incidents show that the average maturity at PT XYZ is at level 3-Defined, which means the distribution of documentation covering all processes.